A New Method For Combining Lead Isotope and Lead Abundance Data to Characterize Archaeological Copper Alloys*. (28th November 2014) - Pollard, A. M.; Bray, P. J.
<x xml:space="preserve">Abstract</x> We present a new methodology for interpreting lead isotope data from archaeological copper alloy objects. It is not based on the conventional isotope ratio biplots, which were originally devised to allow the calculation of the geological age of the lead mineralization, but is derived from isotope mixing models, more often used for presenting strontium isotope data. We illustrate the method by reworking published data on Sardinian Nuragic oxhide ingots and copper alloy artefacts. While we confirm the consensus assumption that the oxhide ingot fragments found on Sardinia are isotopically consistent with Cypriot copper ores (although we see no isotopic reason to favour only Apliki, as originally suggested), we also show that there is evidence for mixing between local and ingot copper in some objects, which was previously not detected. More broadly, we suspect that the apparent mismatch between some source allocations for copper drawn from isotope geochemistry and the rest of the archaeological data in some cases might be due to mixed isotopic signals being incorrectly assigned to a specific source, and suggest that the method presented here will reduce the chances of this happening.